Selenium-associated differentially expressed microRNAs and their targeted mRNAs across the placental genome in two U.S. birth cohorts - Fu-Ying Tian; Elizabeth M. Kennedy; Karen Hermetz; Amber Burt; Todd M. Everson; Tracy Punshon; Brian P. Jackson; Ke Hao; Jia Chen; Margaret R. Karagas; Devin C. Koestler; Carmen Marsit (Epigenetics, 2022)
Selenium is an important micronutrient for foetal development. MicroRNAs play an important role in the function of the placenta, in communication between the placenta and maternal systems, and their expression can be altered through environmental and nutritional cues. To investigate the associations between placental selenium concentration and microRNA expression in the placenta, our observational study included 393 mother-child pairs from the New Hampshire Birth Cohort Study (NHBCS) and the Rhode Island Child Health Study (RICHS). Placental selenium concentrations were quantified using inductively coupled plasma mass spectrometry, and microRNA transcripts were measured using RNA-seq. We fit negative binomial additive models for assessing the association between selenium and microRNAs. We used the microRNA Data Integration Portal (mirDIP) to predict the target mRNAs of the differentially expressed microRNAs and verified the relationships between miRNA and mRNA targets in a subset of samples using existing whole transcriptome data (N = 199). We identified a non-monotonic association between selenium concentration and the expression of miR-216a-5p/miR-217-5p cluster (effective degrees of freedom, EDF = 2.44 and 2.08; FDR = 3.08 × 10−5) in placenta. Thirty putative target mRNAs of miR-216a-5p and/or miR-217-5p were identified computationally and empirically and were enriched in selenium metabolic pathways (driven by selenoprotein coding genes, TXNRD2 and SELENON). Our findings suggest that selenium influences placental microRNA expression. Further, miR-216a-5p and its putative target mRNAs could be the potential mechanistic targets of the health effect of selenium.